2008
DOI: 10.1371/journal.ppat.0040025
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Bases for the Inhibition of Autophagy and Apoptosis by Viral BCL-2 of Murine γ-Herpesvirus 68

Abstract: All gammaherpesviruses express homologues of antiapoptotic B-cell lymphoma-2 (BCL-2) to counter the clearance of infected cells by host antiviral defense machineries. To gain insights into the action mechanisms of these viral BCL-2 proteins, we carried out structural and biochemical analyses on the interactions of M11, a viral BCL-2 of murine γ-herpesvirus 68, with a fragment of proautophagic Beclin1 and BCL-2 homology 3 (BH3) domain-containing peptides derived from an array of proapoptotic BCL-2 family protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
206
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(225 citation statements)
references
References 50 publications
12
206
1
Order By: Relevance
“…The viral Bcl-2 homologue M11 partially disrupts the Beclin 1 homo-oligomer. 15 Interestingly, viral Bcl-2 binds independently to two sites on the Beclin 1 dimer, one with high affinity and one with lower affinity, whereas human Bcl-XL binds to both sites equally with relatively low affinity by sedimentation equilibrium and velocity analysis. 14 Beclin 1 self-interaction is not affected by amino acid deprivation, rapamycin-induced autophagy, PI3KC3/Vps34, Bcl-XL or UVRAG overexpression in live cells.…”
Section: Beclin 1 Is a Bh3-only Domain Autophagy Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…The viral Bcl-2 homologue M11 partially disrupts the Beclin 1 homo-oligomer. 15 Interestingly, viral Bcl-2 binds independently to two sites on the Beclin 1 dimer, one with high affinity and one with lower affinity, whereas human Bcl-XL binds to both sites equally with relatively low affinity by sedimentation equilibrium and velocity analysis. 14 Beclin 1 self-interaction is not affected by amino acid deprivation, rapamycin-induced autophagy, PI3KC3/Vps34, Bcl-XL or UVRAG overexpression in live cells.…”
Section: Beclin 1 Is a Bh3-only Domain Autophagy Proteinmentioning
confidence: 98%
“…vBcl-2 of g-herpesviruses including KSHV and M11 can inhibit autophagy via a direct interaction with Beclin 1 (Pattingre et al 31 ). The M11 has higher affinity to Beclin 1 when compared with other vBcl-2 (Ku et al 15 ; Sinha et al 66 ). The herpes simplex virus protein ICP34.5 interacts with Beclin 1 to block double-stranded RNA-activated protein kinase R-dependent macroautophagy induction, which limits neurovirulence by HSV-1 (Orvedahl et al 67 ).…”
Section: Slammentioning
confidence: 99%
“…The use of the 36-mer BH3 peptides was based on the ample structural, biochemical and cellular data demonstrating that a BH3 domaincontaining segment with < 34 amino acids of the BH3-only proteins is responsible for their interactions with the antiapoptotic BCL-2 relatives [8,9,15,20,21]. The quantification showed that BCL-2 and BCL-w interact tightly with the BAX peptide, exhibiting the K D of 15.1 and 22.9 nM, respectively, while BCL-X L and MCL-1 bind the peptide with lower affinity ( Figure 1A).…”
Section: Preferential Binding Affinity Of Bcl-2 and Bcl-w For Bax Ovementioning
confidence: 99%
“…Interestingly, biochemical studies showed that the Beclin BH3 domain exhibited the weakest interaction among interacting partners of Bcl-XL. The importance of the interaction between Beclin1 BH3 domain and Bcl-2 proteins in autophagy is further highlighted by its exploitation by the viral Bcl-2 protein M11 (Ku et al, 2008). The crystal structure of murine gamma Herpes virus 68 M11 protein in complex with Beclin1 BH3 domain revealed strong interactions analogous to those observed in other Bcl-2 -BH3 complexes.…”
Section: The Phosphatidylinositide-3-kinase Complexmentioning
confidence: 92%